2019
DOI: 10.4103/jfmpc.jfmpc_346_19
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic profile and clinical practices in urinary tract infections in a tertiary care center in Southern India

Abstract: Context:Studies reported differences in clinical profiles of urinary tract infections (UTIs) in patients with and without type 2 diabetes mellitus (T2DM). Studies on the impact of the pattern of antibiotic resistance of organisms causing UTI on actual clinical practice are lacking.Objectives:1. To study the clinical and microbiologic profiles of UTIs. 2. To compare treatment given with the prevailing antimicrobial sensitivity.Settings and Design:This is a cross-sectional study conducted in a tertiary care hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…A study that is very much in line with our findings was conducted in Sudan, which also found E. coli (56.4%), Klebsiella pneumonia (23.0%), and Enterococcus faecalis (12.8%) to be the most common organisms [17]. A study conducted in Southern India among diabetic patients had similar organisms cultured from their patients, but with dissimilar frequencies [22,29]. Klebsiella pneumonia (42.4%), E. coli (21.2%), and Enterococcus faecalis (12.1%) were isolated in the study in Nigeria [22], while E. coli (67%), Enterococcus (9%), and Klebsiella (14%) were found in the study conducted in Southern India [29].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A study that is very much in line with our findings was conducted in Sudan, which also found E. coli (56.4%), Klebsiella pneumonia (23.0%), and Enterococcus faecalis (12.8%) to be the most common organisms [17]. A study conducted in Southern India among diabetic patients had similar organisms cultured from their patients, but with dissimilar frequencies [22,29]. Klebsiella pneumonia (42.4%), E. coli (21.2%), and Enterococcus faecalis (12.1%) were isolated in the study in Nigeria [22], while E. coli (67%), Enterococcus (9%), and Klebsiella (14%) were found in the study conducted in Southern India [29].…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted in Southern India among diabetic patients had similar organisms cultured from their patients, but with dissimilar frequencies [ 22 , 29 ]. Klebsiella pneumonia (42.4%), E. coli (21.2%), and Enterococcus faecalis (12.1%) were isolated in the study in Nigeria [ 22 ], while E. coli (67%), Enterococcus (9%), and Klebsiella (14%) were found in the study conducted in Southern India [ 29 ]. Zhanel et al found a prevalence of E. coli (52.9%) that is similar to ours, but also isolated Streptococcus species (11.4%) and Staphylococcus species (5.9%) in their study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nigussie et al ., found that E. coli was sensitive to nitrofurantoin (100%), norfloxacin (90.9%), ciprofloxacin (81.8%), but resistant to Ampicillin (100%), trimethoprim-sulfamethoxazole (81.8%), gentamicin (72.7%). [ 43 ] This study also showed that E. coli was resistant to Gentamicin (72.7%),[ 42 ] but our study showed it was susceptible to Gentamicin (66.7%). The resistance of E. coli in this study to Ampicillin was 100%,[ 43 ] compared to our results which shows a resistance of 86.04%.…”
Section: Discussionmentioning
confidence: 53%
“…[ 31 ] Klebsiella pneumonia (42.4%), E. coli (21.2%), and E. faecalis (12.1%) were isolated from the study in Nigeria,[ 19 ] while E. coli (67%), Enterococcus (9%), Klebsiella (14%) were found in the study conducted in Southern India. [ 42 ] Odetoyin et al ., performed a study where the isolated organisms were Staphylococcal aureus (80.9%), Klebsiella (9.5%), Enterococcus faecalis (4.8%), and E. coli (4.8%). [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance is significant, with varying resistance rates to common antibiotics, presenting a pressing challenge [ 15 ]. In South India and Sri Lanka, high resistance rates to antibiotics like quinolones and penicillins have been reported, though some, like imipenem, retain effectiveness [ 3 , 16 ].…”
Section: Introductionmentioning
confidence: 99%